Incidence of bone stress injury is greater in competitive female distance runners with menstrual disturbances independent of participation in plyometric training. Issue 22 (17th November 2021) - Hutson, Mark J; O'Donnell, Emma; Petherick, Emily; Brooke-Wavell, Katherine; Blagrove, Richard C
ABSTRACT: Bone stress injury (BSI) is prevalent in female distance runners. Menstrual disturbances are associated with impaired bone health in endurance athletes. This study aimed to investigate the association between menstrual function and BSI and explore whether plyometric training may protect against BSI in individuals with menstrual disturbances. Competitive female distance runners (n = 183) aged 18–40 years were surveyed for training habits, menstrual function, and BSI, during the previous 12 months. Oligo/amenorrhoea during the previous 12 months (<9 menses) was deemed to indicate menstrual disturbance; hormonal contraceptive users and those previously diagnosed with a pathology that impacted menstrual function were excluded. BSI incidence rate was 2.25 ( p = 0.02, 95% CI: 1.14–4.41) times greater in oligo/amenorrhoeic than eumenorrhoeic runners. BSI incidence rate was similar in oligo/amenorrhoeic and eumenorrhoeic runners that did plyometric training, but 3.78 ( p = 0.001, 95% CI: 1.68–8.5) times greater in oligo/amenorrhoeic versus eumenorrhoeic runners that did not. However, the effect of plyometrics was non-significant (menstrual function × plyometric training interaction, p = 0.06; main effect, p = 0.89). Conventional plyometric training may not reduce BSI incidence in female distance runners, but menstrual disturbances and prolonged periods of low energy availability should be avoided.